Potential Risk Areas of Aedes albopictus in South-Eastern Iran: A Vector of Dengue Fever, Zika, and Chikungunya - Nejati, Jalil; Bueno-Marí, Rubén; Collantes, Francisco; Hanafi-Bojd, Ahmad A.; Vatandoost, Hassan; Charrahy, Zabihollah; Tabatabaei, Seyed M.; Yaghoobi-Ershadi, Mohammad R.; Hasanzehi, Abdolghafar; Shirzadi, Mohammad R.; Moosa-Kazemi, Seyed H.; Sedaghat, Mohammad M. (Frontiers in Microbiology, 2017)
The possibility of the rapid and global spread of Zika, chikungunya, yellow fever and dengue fever by Aedes albopictus is well documented and may be facilitated by changes in climate. To avert and manage health risks, climatic and topographic information can be used to model and forecast which areas may be most prone to the establishment of Ae. albopictus. We aimed to weigh and prioritize the predictive value of various meteorological and climatic variables on distributions of Ae. albopictus in south-eastern Iran using the Analytical Hierarchy Process. Out of eight factors used to predict the presence of Ae. albopictus, the highest weighted were land use, followed by temperature, altitude and precipitation. The inconsistency of this analysis was 0.03 with no missing judgments. The areas predicted to be most at risk of Ae. albopictus-borne diseases were mapped using Geographic Information Systems and remote sensing data. Five-year (2011–2015) meteorological data was collected from 11 meteorological stations and other data was acquired from Landsat and Terra satellite images. Southernmost regions were at greatest risk of Ae. albopictus colonization as well as more urban sites connected by provincial roads. This is the first study in Iran to determine the regional probability of Ae. albopictus establishment. Monitoring and collection of Ae. albopictus from the environment confirmed our projections, though on-going field work is necessary to track the spread of this vector of life-threatening disease.